Enabling Continuous Quality Improvement in Practice: The Role and Contribution of Facilitation - Harvey, Gillian; Lynch, Elizabeth (Frontiers in Public Health, 2017)
Facilitating the implementation of continuous quality improvement (CQI) is a complex undertaking. Numerous contextual factors at a local, organisational and health system level can influence the trajectory and ultimate success of an improvement program. Some of these contextual factors are amenable to modification, others less so. As part of planning and implementing healthcare improvement, it is important to assess and build an understanding of contextual factors that might present barriers to or enablers of implementation. On the basis of this initial diagnosis, it should then be possible to design and implement the improvement intervention in a way that is responsive to contextual barriers and enablers, often described as ‘tailoring’ the implementation approach. Having individuals in the active role of facilitators is proposed as an effective way of delivering a context-sensitive, tailored approach to implementing CQI. This paper presents an overview of the facilitator role in implementing CQI. Drawing on empirical evidence from the use of facilitator roles in healthcare, the type of skills and knowledge required will be considered, along with the type of facilitation strategies that can be employed in the implementation process. Evidence from both case studies and systematic reviews of facilitation will be reviewed and key lessons for developing and studying the role in the future identified.